Peningkatan Produktivitas Kerja Melalui Penerapan Sistem Informasi Kinerja Pegawai Dan Remunerasi (SIJAWARA) - Septiani, Tia; Meilani, Rini Intansari; Inayati, Tutik (Universitas Pendidikan Indonesia, 2024)
The development of information technology today brings the impact of changes that require organizations to continue to develop in accordance with the goals and policies that have been determined. The problem that often occurs in organizations is the use of technology that is not optimal, so that it can affect the level of employee productivity in the organization. This study aims to determine the effect of Employee Performance Information System and Remuneration (SIJAWARA) on employee work productivity. This study uses quantitative methods, with data collection through distributing questionnaires to 48 employees of the State Civil Apparatus (ASN) at the Fisheries Service in West Java. The results of the descriptive analysis indicate that the SIJAWARA variable is in the moderately effective category, and the employee work productivity variable is in the low category. The results of the inferential analysis show that there is an influence between the SIJAWARA variable on the employee work productivity variable, but with a relatively low relationship category.